Review of geomagnetically induced currents - Wanye Bu; Huiqian Zhang; Qinghua Huang (地球与行星物理论评, 2022)
Geomagnetic disturbances caused by solar activities induce geoelectric fields on the earth's surface, which generate geomagnetically induced currents (GICs) in electrically conducting systems. Magnetic storms caused by anomalous solar activities produce strong GICsthat posing severe threats to the security operations of telecommunication systems, electric power grids, oil and gas pipelines, railway transportation networks and other infrastructure systems, and represent one of the most serious space weather hazards. Therefore, studying GICs for the purpose of rapid GICs forecasting has both scientific as well as practical significances. In this article, we review the development of GICs-related research. We begin by introducing the concept of space weather chain in which GICs are the final link of the space weather chain involving the solar activity, the solar wind, and geomagnetic disturbance. Then we focus on the three steps in GICs calculation: reconstruction of the geomagnetic field, calculation of induced geoelectric field, and modeling of GICs in ground electrically-conducting systems. Major techniques as well as related theories and applications used in each step are summarized and evaluated. Finally, we also provide assessments of the current status of GICs research, and outlook of its future directions and major challenges.